"\\frac{dx}{x^2+y^2}=\\frac{dy}{2xy}=\\frac{dz}{z(x+y)}"
1) "\\frac{dx+dy}{x^2+y^2+2xy}=\\frac{dz}{z(x+y)}"
"\\frac{dx+dy}{(x+y)^2}=\\frac{dz}{z(x+y)}, \\quad \\frac{dx+dy}{x+y}=\\frac{dz}{z} ,\\quad d(\\ln |x+y|)=d(\\ln |z|)"
"\\ln |x+y|=\\ln|z|+C"
"|x+y|=e^C|z|"
"x+y=\\hat {C}z"
2) "\\frac{dx-dy}{x^2+y^2-2xy}=\\frac{dz}{z(x+y)}"
"\\frac{dx-dy}{(x-y)^2}=\\frac{dz}{ \\hat{C} z^2}, \\quad d(\\frac{-1}{x-y})=d(\\frac{-1}{\\hat{C}z})"
"\\frac{-1}{x-y}=\\frac{-1}{\\hat{C}z}+C\u2019=\\frac{-1}{x+y}+C\u2019"
"\\frac{1}{x+y}-\\frac{1}{x-y}=\\frac{-2y}{x^2-y^2}=C\u2019"
Answer: "x+y=C_1z, \\; \\frac{-2y}{x^2-y^2}=C_2"
Comments
Leave a comment